Intensifying production among smallholder farmers: The impact of improved climbing beans in Rwanda - Sperling, L.; Munyanesa, S (1995)
While bush beans ( Phaseolus vulgaris check for this species in other resources L.) have long been the protein staple of Rwandan agriculture, improved climbing beans have been introduced within the last 10 years, enabling farmers to intensify, stabilize and better stagger production. Through a 1992-3 nation-wide survey of 1050 households, conducted in both major growing seasons, this study examines the adoption of improved climbing beans across regions and potential user groups. Use of improved climbing beans, by 500,000 households, cross-cuts farm size, economic class and gender boundaries, and is most intensive among the more disadvantaged. Initial concerns with staking material, how to obtain and manage it, have posed relatively few problems for farmers, and the surprising plasticity of improved climbers has encouraged research to more closely determine soil fertility demands. Increased incidence of root rot ( Fusarium oxysporum check for this species in other resources ) and fear of reduced genetic variability on-farm have resulted in the Institut des Sciences Agronomique du Rwanda (ISAR's) adopting targeted pathogen screening procedures and releasing many new cultivars simultaneously. The success of improved climbers, bringing Rwanda an additional US$ 8 to 15 million per year, has stimulated promising R & D efforts in Kivu, Zaire and southern Burundi, and several other Eastern African regions have been identified as prime for climbing bean introduction.